1996
DOI: 10.1046/j.1471-4159.1996.67010037.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Subunits in the Mouse Cochlea

Abstract: Messages for subunits of voltage-gated calcium channels were examined in the cochlea of the CBAm ouse by PCR analysis. Total RNA was extracted from the auditory organs of 16-18-day-old animals. After reverse transcription, resulting cDNA was amplified by PCR with primers targeted to nucleotide sequences corresponding to 12 different calcium channel subunits. PCR products representing subunit gene expression were strongly and consistently amplified for aic, a 10, alE, /3~,/33, and /3~but not for alA, aiB, ais, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 66 publications
3
30
1
Order By: Relevance
“…Likewise, Song et al (2003) and others have suggested that muted CDI may partially arise from ␣ 1 subunit association with different auxiliary subunits (␣ 2 ␦ and ␤) or presynaptic proteins. Previous reports showed that the mouse cochlea expressed Ca V 1.2, Ca V 1.3, Ca V 2.3, and auxiliary subunits ␣ 2 ␦, ␤ 1 , ␤ 3 , and ␤ 4 (Green et al, 1996;Song et al, 2003). The auxiliary subunits when coexpressed with the ␣ 1 subunits modulate the kinetics and properties of channel gating (Lacerda et al, 1991;Singer et al, 1991;Varadi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Song et al (2003) and others have suggested that muted CDI may partially arise from ␣ 1 subunit association with different auxiliary subunits (␣ 2 ␦ and ␤) or presynaptic proteins. Previous reports showed that the mouse cochlea expressed Ca V 1.2, Ca V 1.3, Ca V 2.3, and auxiliary subunits ␣ 2 ␦, ␤ 1 , ␤ 3 , and ␤ 4 (Green et al, 1996;Song et al, 2003). The auxiliary subunits when coexpressed with the ␣ 1 subunits modulate the kinetics and properties of channel gating (Lacerda et al, 1991;Singer et al, 1991;Varadi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed that Ca V 1.3 splice variants may be involved (Green et al, 1996;Kollmar et al, 1997a,b;Ramakrishnan et al, 2002). In particular, Ca V 1.3 of the chicken basilar papilla (Kollmar et al, 1997a,b) has an additional 26 amino acids within the I-II loop region (exon 9a) of Ca V 1.3, and the I-II loop has been proposed as a "hinged lid" to obstruct the channel pore and bring about inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal was to test whether known Ca 2ϩ channel subunits that can be expressed functionally are sufficient to produce the properties of L-type current in hair cells. The ␤ 1A subunit is expressed abundantly in hair cells, but ␤ 2A is not (Green et al 1996). To allow detection of transfected cells, the S65T bright green fluorescent protein (GFP) mutant in GFPpRK5 vector was used to co-transfect the cells to quantify the transfection efficiency.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Both phenomena exacerbate with age, and are associated, for instance, with impaired speech intelligibility. Studies of the inner ear revealed expression of Ca v 1.2 in the auditory nerve and inhibitory efferents projecting to the OHCs [11,31].…”
Section: Ca V 12 and Hearing Damagementioning
confidence: 99%